DIGITAL ENTREPRENEURIAL ECOSYSTEMS AND MARKET EXPANSION: A STRATEGIC PERSPECTIVE ON SME COMPETITIVENESS - Hery Margono (KOMITMEN: Jurnal Ilmiah Manajemen, 2024)
The development of the digital entrepreneurial environment has driven significant changes in business interaction patterns, making them increasingly connected, dynamic, and geographically unbounded. This situation opens up broader opportunities for small and medium-sized businesses to expand their market reach, but also introduces new complexities in facing increasingly open competition. On the other hand, business actors' ability to respond to these changes still shows significant variation, particularly in terms of technology utilization, access to information, and adaptive strategic management. This study aims to examine the relationship between the dynamics of the digital entrepreneurial environment and market expansion strategies and their implications for strengthening business actors' competitiveness. This study uses a qualitative approach, utilizing various relevant secondary data sources for in-depth analysis. The results indicate that the intensity of connectivity and network utilization in the digital environment play a crucial role in opening access to broader market opportunities. Success in market expansion is strongly influenced by business actors' ability to develop flexible, integrated, and responsive strategies to change. Furthermore, strengthening competitiveness is determined by the ability to integrate various strategic elements, including internal resource management, exploiting external opportunities, and adapting to evolving environmental dynamics.